System and method for activity monitoring eyeware and head apparel - Chang, A. R.; Wang, C.-C.; Cowan, R. F. (Free Patents Online: United States Patent Application 20180125423, 2018)
A system and method for activity monitoring eyewear and head apparel can include collecting kinematic data from an activity monitoring system that is coupled to a user head region; generating a set of activity signals that comprises at least one head orientation signal that is at least partially generated from the kinematic data head orientation signal from the kinematic data; monitoring the set of activity signals for a response condition; and triggering an action response upon detection of the response condition.